Design and Analysis Effect of Gantry Angle Photon Beam 4 MV on Dose Distributions using Monte Carlo Method EGSnrc Code System - Uum Yuliani; Ridwan Ramdani; Freddy Haryanto; Yudha Satya Perkasa; Mada Sanjaya (Institut Teknologi Bandung, 2016)
Varian linac modeling has been carried out to obtain Percentage Depth Dose (PDD) and profiles using variations gantry angle 0o, 15o, 30o , 45o in the vertical axis of the surface, field size 10x10 cm2, photon beam 4 MV and Monte Carlo simulations. Percentage Depth Dose and profile illustrates dose distributions in a phantom water measuring 40x40x40 cm3, changes gantry is one of the factors that determine the distribution of the dose to the patient research shows changes in Dmax in the Percentage Depth Dose is affected by changes in the angle gantry resulted in the addition of the area build up so it can be used for therapy in the region and produce skin sparing effects that can be used to protect the skin from exposure to radiation. The graph result is profiles obtained show lack simetrisan in areas positive quadrant has a distribution of fewer doses than the quadrant of negative as well as the slope of the surface so that it can be used for some cases treatments that require a depth and a certain slope, dose calculations are more accurate and can minimize side effects.